oqxAB-Positive IncHI2 Plasmid pHXY0908 Increase Salmonella enterica Serotype Typhimurium Strains Tolerance to Ciprofloxacin - Lian, Xinlei; Wang, Xiran; Liu, Xiao; Xia, Jing; Fang, Liangxing; Sun, Jian; Liao, Xiaoping; Liu, Yahong (Frontiers in Cellular and Infection Microbiology, 2019)
Salmonella enterica serotype Typhimurium is a major global food-borne pathogen and causes life-threatening infections. Although the resistance mechanisms to fluoroquinolones in S. Typhimurium had been well-defined, tolerance to fluoroquinolones and the associated mechanism for this are obscure. In the current work, we investigated an oqxAB-positive plasmid pHXY0908 and analyzed its role in S. Typhimurium tolerance to ciprofloxacin using time-kill, transcriptome sequencing and real-time PCR. S. Typhimurium ATCC14028 could survive under lethal concentrations of ciprofloxacin after acquiring plasmid pHXY0908. Transcriptome sequence analysis showed the chromosomal genes were systematically regulated after acquiring this plasmid suggesting an interaction between chromosome and plasmid. Additionally, the chromosomal efflux pump genes acrB, acrA, tolC, and yceE were up-regulated after acquiring plasmid pHXY0908 suggesting that these efflux pumps may contribute to the survival of ATCC14028 exposed to the lethal concentrations of ciprofloxacin. In conclusion, this is the first known report demonstrating that an IncHI2 type plasmid harboring oqxAB could assist S. Typhimurium survival under lethal concentrations of ciprofloxacin.